EXPLORING THE ROLE OF POSYANDU CADRES: A CASE STUDY ON RAISING AWARENESS OF BALANCED NUTRITION AMONG PREGNANT WOMEN - Siti Fatimah, Okta Zenita; Hidayah, Seventina Nurul (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
Posyandu is one form of Community-Sourced Health Efforts that plays an important role in improving maternal and child health quality, including providing education related to balanced nutrition during pregnancy. This study aims to evaluate the effectiveness of Posyandu cadres in increasing pregnant women's awareness about the importance of balanced nutrition during pregnancy in Baru Village, Rebo Subdistrict, East Jakarta. This qualitative research approach uses a case study design and purposive sampling technique of Posyandu cadres and pregnant women as participants. Data was collected through in-depth interviews and group discussions (FGDs) to gain a thorough understanding. The results showed that Posyandu cadres are effective motivators and educators in delivering balanced nutrition information to pregnant women. In addition, it was found that cadre effectiveness was influenced by cadre education level, support from health facilities, and active participation of pregnant women. The implications of this study emphasize the importance of ongoing training for Posyandu cadres and increased collaboration between cadres and health workers to ensure pregnant women receive accurate and relevant nutrition information, ultimately contributing to maternal and infant health.